Supervisi dan Pengembangan Profesional Guru - Mutiara Sani; Meti Fatimah (Lembaga Yasin AlSys, 2026)
Changes in the paradigm and authority of educational supervision are important aspects of improving educational quality because they determine the patterns of guidance, oversight, and professional development for teachers. This study aimed to analyse the paradigm and authority of educational supervision and examine the relationship between the two in improving educational quality. This study employed a descriptive qualitative approach using library research through a review of books, scientific journal articles, policy documents, and various sources of literature relevant to educational supervision. The data were analysed through the stages of data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the development of the supervision paradigm and the application of authority in educational practice. The findings showed that the educational supervision paradigm had shifted from an authoritarian inspection approach to collaborative, humanistic, and transformational approaches oriented towards the continuous professional development of teachers. This shift also transformed supervisory authority from a hierarchical, control-based pattern into participatory professional leadership grounded in competence, integrity, and the ability to empower teachers. In the context of modern education, supervision functions not only as an oversight mechanism but also as a strategic instrument for enhancing teacher professionalism, strengthening instructional leadership, building professional learning communities, and supporting educational transformation in the digital era. This study confirms that the effectiveness of supervision is determined by the alignment between a collaborative paradigm and the professional, ethical, and participatory exercise of authority. These findings provide a conceptual contribution to the development of educational supervision and practical implications for supervisors and leaders of educational institutions in integrating professional leadership, collaboration, ethics, and the use of technology into efforts to sustainably improve educational quality.